“MUCH OF OUR COUNSELLING IS ABOUT YOUR FACIAL EXPRESSION AND AUTHENTICITY”: SCHOOL-BASED COUNSELLING DURING COVID-19 IN KWAZULU-NATAL PROVINCE - Warria, Ajwang’; Coleman, Kerry-Jane; Chadambuka, Cyndirela (Social Work, 2023)
Maintaining therapeutic care of learners during and after COVID-19 in South Africa has required significant changes to the way that counselling is provided in schools. While some of these changes are well documented, there are critical gaps regarding the experiences of school counsellors during the pandemic period, globally and in South Africa. Hence this qualitative study sought to explore the experiences of school psychosocial practitioners who are rendering supportive services in private schools in KwaZulu-Natal Province. While the findings show that remote/online therapy is a valid option, all schools should ensure that therapists have adequate resources and the necessary collaboration to provide effective services to the school community. Furthermore, interpersonal, organisational, practice, policy and advocacy-oriented adaptations are required in establishing transformative interventions in all schools to address trauma. Keywords: counselling, COVID-19, psychosocial intervention, schools, South Africa